(untitled) (Modern American Journal of Social Sciences and Humanities, 2025)
This article details the political and legal reasons that led to the formation of the “Durand line” – the border between Afghanistan and Pakistan. The article also discusses in detail the problems that arose as a result of the creation and installation of this line.